EFFECT OF LOW RANK COAL TEMPERATURE AND MOISTURE CONTENT ON SLOW PYROLYSIS PROCESS - Slamet Handoko; Sapta Rianda; Nurhadi Nurhadi (Puslitbang tekMIRA, 2021)
The government of Indonesia has made policies to increase the added value of coal. It can be completed using technology of slow pyrolysis. This study aimed to increase the added value of coal by analyzing the effect of temperature and water content of the feed on slow pyrolysis products. Water content variation in the feed form of coal was 10.57 wt% and 16.86 wt%. Temperature variations in the slow pyrolysis process were 500, 600, 700, and 800 ºC. Result of this research showed that the low moisture content of coal produced more char in the slow pyrolysis process. Based on the variations of the used temperature, a higher temperature of pyrolysis produced fewer char but its calorific value of coal product was also higher. The optimum operating condition was achieved at 500-600 ºC.